Visual and Narrative Engagements with the "Subak" System: A Thematic Analysis of Sustainability Learning through Creative Interpretation in Bali - Kaler Surata, Sang Putu; I Gusti Agung Sri Rwa Jayantini; Ida Bagus Ari Arjaya; Irina Safitri Zen (Jurnal Kajian Bali (Journal of Bali Studies), 2025)
Subak, Bali’s traditional ecological knowledge (TEK) system rooted in Tri Hita Karana, integrates water management, spiritual practice, and communal governance. This study investigates how Singaporean university students engaged with Subak during a cross-cultural, place-based learning program. Through immersive field visits to Subak Pulagan, located about 30 kilometers northeast of Denpasar, students produced drawings and narratives to interpret ecological, cosmological, and social relationships. Using phenomenographic inquiry combined with thematic and factor analysis, six themes were identified: sacred water, spiritual ecology, collective governance, temple networks, sustainability threats, and symbolic meaning. Findings show that students perceived Subak as a dynamic socio-ecological system and demonstrated ethical awareness and intercultural understanding. Framed by Critical Pedagogy of Place, their creative expressions revealed processes of reinhabitation and decolonization. The study underscores the value of arts-based, culturally grounded learning for deepening engagement with Indigenous ecological knowledge in Bali.